Hubungan Tingkat Pengetahuan, Sikap dan Dukungan Tenaga Kesehatan pada Calon Pengantin (Catin) Tentang Penyakit Sifilis di Wilayah Kerja Puskesmas Kotabaru Kecamatan Keritang Kabupaten Inhil Riau Tahun 2023 - Muspa, Rantika; Mariana, Silvia; Ningsih, Nisa Kartika (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Syfillis cases in Southeast Asia in 2015 amounted to 3 million. The areas that have the highest rates of syphilis transmission are Sub-Saharan Africa, the United States and Southeast Asia. Studies conducted in Africa show that there are 30% positive antenatal syphilis cases and 50% result in infant death in congenital syphilis. This research is a type of quantitative research with an analytical observational research design with a cross sectional study approach. The population in this study were all prospective brides and grooms in Keritang District, the working area of the Kotabaru Community Health Center in 2023, as of January, as many as 36 people who had bridal injections (catin) at the Community Health Center. The sampling technique used in the research was accidental sampling. Data was collected using a questionnaire and data processing using the SPSS program. Data analysis in this study was univariate and bivariate analysis using the chi-square test formula with a confidence level of 95% (0.05). The results of the study revealed that the level of knowledge of the prospective bride and groom (catin), the attitude of the prospective bride and groom (catin) and the support of health workers had a value of each variable less than 0.05 or a significance value of p<0.05, which indicated that there was a significant relationship of these three variables in prospective brides (catin) regarding syphilis in the working area of the Kotabaru health center, Keritang District, Inhil Regency, Riau in 2023.